Cancer distress screening data: Translating knowledge into clinical action for a quality response. Issue 1 (13th August 2013) - Howell, Doris; Hack, Thomas F.; Green, Esther; Fitch, Margaret
Abstract Objectives: The purpose of this paper is to summarize the use of the knowledge to action framework for adapting guidelines for practice and the evidence for effective implementation interventions to promote a quality response to cancer distress screening data. Methods: We summarize progress in screening implementation in Ontario, Canada and the application of a systematic approach for adapting knowledge to practice and use of evidence-based knowledge translation interventions to ensure the uptake of best practices to manage distress. Results: While significant progress has been made in the uptake of distress screening it is less clear if this has resulted in improvements in patient outcomes, i.e., reduced distress. The use of evidence-based knowledge translation strategies tailored to barriers at many levels of care delivery is critical to facilitate the uptake of distress screening data by the primary oncology team. Significance of results: There is a wealth of knowledge about the approaches that can be applied to translate knowledge into practice to improve psychosocial care and promote evidence-based distress management by the primary care oncology team. However, further implementation research is needed to advance knowledge about the most effective strategies in the context of cancer care.